ANALYSIS OF CHANGES IN ENVIRONMENTAL LAW AFTER THE ENACTMENT OF THE JOB CREATION LAW - Nobella Indradjaja; Chamdani (Awang Long Law Review, 2023)
Indonesia is a country full of natural resources, which are of extraordinary value in terms of ecology and social. Only, this is not accompanied by regulatory arrangements that are principled in sustainable development goals. The government is an institution that is obliged to ensure that the development is being carried out, although should be profitable in investment terms, must still ensure the preservation of nature. It is just that, because there are so many articles (over capacity) in the act that overlap (over lapping) each other, the government is stuck in a condition to simplify its regulations without paying attention to the preservation side of the environment. This is, evidenced by the use of omnibus law, which is a system of simplifying regulations by revising, changing or deleting articles that are considered inefficient. One of the impacts of this method implementation is the change in the Environmental Protection and Management Law, which is changed into the Job Creation Law, which then revoked by Government Regulation in Lieu of Law Number 2 Year 2022. This law is alleged to have an impact on preservation of the environment due to the loss of the essence of the Environmental Protection and Management Law document importance. Thus, this study focuses on looking at changes in these articles and their impact using the descriptive method of analysis, by discussing existing articles as a basis. The results of this study show that the change of the Environmental Protection and Management Law into the Job Creation Law, which then revoked by Government Regulation in Lieu of Law Number 2 Year 2022, has an impact on Environmental Regulations, Environmental Permits, as well as the preparation of Environmental Protection and Management Law and the provision of environmental impact assessments information to the public.